La incidencia de la matrogimnasia para el mantenimiento motriz de los adultos mayores del barrio Chipoalo parroquia San Miguel cantón Salcedo provincia Cotopaxi durante el año 2014 - Morocho Chamorro, Irma Jimena (2015)
The present investigation work was done by means of the use of different techniques that allowed to gather the necessary information in the Chipoalo neighborhood, Salcedo Canton, because most of residents, specifically the elderly are sedentary due to the lack of sport activities that allow them to interact to each other, for this reason it is underlined the necessity to implement a methodological guide of basic exercises of matrogimnasia for the motor functions maintenance of the elderly, which aims to raise awareness, in such a way that the proposal acts as an alternative to create habits and to renew the quality of daily social living....